Controle de cheias em reservatórios de usinas hidrelétricas - Costa, Joari Paulo da (1982)
Reservoirs operated for conservative purposes are usually kept at their highest possible levels. This conflicts with flood control requirements, which seek to empty a portion of the total volume (flood control storage) in order to be able to store the excess inflow during floods of return period up to 50 years. The objetive of this work is to calculate the maximum storage allowed in the reservoir constrained by a predeterminated risk of downstream flooding (emergency). The flood control storage is usually calculated based on simulation or in the volume-duration method. This thesis proposes the critical volume method that determines, for each day of the rainy season, the flood control storage necessary to keep the emergency probability equal to a pre-established value (target risk). This method uses a backward recursion scheme over synthetic flow sequences. A case study with Furnas reservoir (Grande river) is presented. The flood control storage volumes in a reservoir system can be allocated in many alternative ways, so that each reservoir shares the responsibility for valley protection. In this work, it is proposed the allocation that minimizes the loss of energy generation capability while keeping the flood risk below the target risk. The selected objective function is to maximize the expected value of the stored energy in the hydroelectric system at the beginning of the dry season. It is developed an approximate approach for defining the objective function through the volume-duration method. The approximation results in a non-linear optimization problem with linear constraints. This method is used in a case study with the reservoir system of the Grande and Paranaíba rivers and the power plants of Ilha Solteira and Jupiá.